2009
DOI: 10.1111/j.1365-2788.2009.01154.x
|View full text |Cite
|
Sign up to set email alerts
|

‘It's pretty hard with our ones, they can't talk, the more able bodied can participate’: staff attitudes about the applicability of disability policies to people with severe and profound intellectual disabilities

Abstract: The study suggests more focused attention is needed to staff understanding the values embedded in current policies and their application to people with more severe disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 23 publications
7
87
0
5
Order By: Relevance
“…Although not directly discussed by service users, their desire for consistent routines and the importance of appropriate staff attitudes may support the requirement for supervision and feedback. While in interviews with a number of supervisors, support workers' resistance to engaging in the process was confirmed, critical studies in the literature indicate that supervision and feedback is a significant requirement for delivering quality ID services (Berkery et al, 2009;Bigby et al, 2009;Clement & Bigby, 2008;Mansell, 2006;Mansell et al, 2008;Skirrow & Hatton, 2007;West et al, 2006).…”
Section: Management Practicesmentioning
confidence: 99%
See 4 more Smart Citations
“…Although not directly discussed by service users, their desire for consistent routines and the importance of appropriate staff attitudes may support the requirement for supervision and feedback. While in interviews with a number of supervisors, support workers' resistance to engaging in the process was confirmed, critical studies in the literature indicate that supervision and feedback is a significant requirement for delivering quality ID services (Berkery et al, 2009;Bigby et al, 2009;Clement & Bigby, 2008;Mansell, 2006;Mansell et al, 2008;Skirrow & Hatton, 2007;West et al, 2006).…”
Section: Management Practicesmentioning
confidence: 99%
“…Elgi, Feurer, Roper and Thompson (2002) determined that positive staff attitudes towards community inclusion of people with ID was significant to staff-initiated social interactions, which in turn was significant to community activities. In the Australian context, Bigby et al (2009) concluded that staff attitudes that were reflective of values underpinning policy and service delivery goals were enabling of service user outcomes.…”
Section: Staff Attitudesmentioning
confidence: 99%
See 3 more Smart Citations